Business Politics-Incorporating Factor of Slovenske Zeleznice Holding in European Traffic Flows - Pirš, Bojan (Promet - Traffic&Transportation, 2004)
The joining of the Republic of Slovenia in the EuropeanUnion gives special significance to the economic subjects becausethe past market and competition are open directly for theSlovenian economic subjects. It means that competition will increasefor the market of transport service. There will be morepossibilities for the enterprises to move faster towards culmination,the phase of degeneration - crisis. Since the business crisisendangers the future existence and development of the Slovenskeieleznice Holding, it has become very important to be ableto control it. In order to avoid this, the Slovenske ielezniceHolding needs clear and methodical business politics whichmeans common interconnections and interacting influence ofelements (rules, criteria, measures and activities), which constantlymove, change and develop. The business politics givesaims and feedback as a condition for the existence and functioningof everything, so it cannot be regarded only as a globalprogramme of development, but rather as a very complex anddynamic system.The elements of the business politics model- incorporatingfactor to the European traffic flows are the sub-politics of thebusiness politics which influence its realisation; production,staff, marketing, finances and development sub-politics. Theevaluation of the elements of the model has taken into considerationtheir condition and meaning in the realisation of the businesspolitics in 2003 and their expected values in 2008, whensimple transmission of achievements is expected in the railwaytraffic in the European Union and in the year 2012 when a repeatedenlargement of the European Union is foreseen.The model of business politics -factor of integration of theSlovenske ieleznice Holding into the European traffic flows isan experiment to restore the collaborating relation between certainelements of the model.